Endogenous hydrogen sulfide is involved in osteogenic differentiation in human periodontal ligament cells. (August 2016) - Cen, Sheng-Dan; Yu, Wen-Bin; Ren, Man-Man; Chen, Li-Jiao; Sun, Chao-Fan; Ye, Zhi-Li; Deng, Hui; Hu, Rong-Dang
Highlights: CBS and CSE produce H2 S in hPDLCs to promote their osteogenic differentiation. Optimal concentrations of endogenous H2 S must be maintained. Excessive or deficient H2 S levels temper the observed osteogenic effect. These effects are exerted by activating the Wnt/β-catenin signaling cascade. Abstract: Objective: Endogenous hydrogen sulfide (H2 S) has recently emerged as an important intracellular gaseous signaling molecule within cellular systems. Endogenous H2 S is synthesized froml -cysteine via cystathionine β-synthase and cystathionine γ-lyase and it regulates multiple signaling pathways in mammalian cells. Indeed, aberrant H2 S levels have been linked to defects in bone formation in experimental mice. The aim of this study was to examine the potential production mechanism and function of endogenous H2 S within primary human periodontal ligament cells (PDLCs). Design: Primary human PDLCs were obtained from donor molars with volunteer permission. Immunofluorescent labeling determined expression of the H2 S synthetase enzymes. These enzymes were inhibited with D, L-propargylglycine or hydroxylamine to examine the effects of H2 S signaling upon the osteogenic differentiation of PDLCs. Gene and protein expression levels of osteogenic markers in conjunction with ALP staining and activity and alizarin red S staining of calcium deposition were used to assay the progression of osteogenesis under different treatment conditions. Cultures were exposed to Wnt3a treatment to assess downstream signaling mechanisms. Results: In this study, we show that H2 S is produced by human PDLCs via the cystathionine β-synthase/cystathionine γ-lyase pathway to promote their osteogenic differentiation. These levels must be carefully maintained as excessive or deficient H2 S levels temper the observed osteogenic effect by inhibiting Wnt/β-catenin signaling. Conclusions: These results demonstrate that optimal concentrations of endogenous H2 S must be maintained within PDLCs to promote osteogenic differentiation by activating the Wnt/β-catenin signaling cascade.